Predictors of Family Stress in Taking Care of Patients with Schizophrenia - Rizki Fitryasari; Nursalam Nursalam; Ah Yusuf; Rachmat Hargono; Chong-Mei Chan (Universitas Airlangga, 2018)
Introduction: Taking care of schizophrenia patients is challenging and causes stress for the family involved. The study was conducted to identify the predictors of family stress present when taking care of a patient with schizophrenia. The ABCX Stress Theory of Hill was used as the theoretical framework.Methods: This study used a correlational design. The sample was 137 families who were caring for patients with schizophrenia at the Menur Mental Hospital, Surabaya, Indonesia. The sample was obtained by way of purposive sampling. The data was collected by a questionnaire and analysed by multiple regression to determine the relationship of the family’s structure, family knowledge, the burden of care, stigma, social support, the patient's illness duration, the patient’s frequency of relapse and the patient's severity level with family stress.Results: The results showed that the family’s stress was predicted by the family’s structure (p=0.029), stigma (p=0.000), the burden of care (p=0.000), and the patient’s frequency of relapse (p=0.005). The burden of care was the strongest predictor of family stress (Beta= 0.619).Conclusion: The patient's frequency of relapse and stigma were other kinds of family stressor. The stressors stimulated a negative perception, called the care burden. Limited adequacy of the family structure-function will inhibit the family in using other resources, creating family stress. Nurses may develop an assessment format that consists of the family stress predictors in order to create a nursing care plan specific to reframing the techniques of family stress management.